What Happens After the Storm? Investigating Three Conditions Under Which Local Governments Change Integrity Policy After Scandals. (1st October 2016) - Grimmelikhuijsen, Stephan; Snijders, Berend
Abstract : Integrity violations often generate political scandals, but what conditions determine whether this eventually leads to the improvement of integrity measures and policies? This article analyzes integrity scandals of 17 Dutch municipalities in the period 2006–2010 using qualitative comparative analysis. Three conditions are taken into consideration: media attention, presence of external audits, and involvement of civil servants in the violation. First, the results describe that in nearly half the cases nothing changed at all after a scandal. Second, this study explains why integrity policies changed—or remain the same. The analysis shows that changes are more likely when other civil servants are involved in a scandal and that the presence of an external audit helps to create a window of opportunity for change. On the other hand, more intense media coverage was not a sufficient condition for change in integrity policy. The study concludes that a scandal alone is not enough to create a window of opportunity for change, but that particular conditions need to be present—most notably external audits and involvement of other civil servants in the violation.